Benzoxazole-Based Metal Complexes to Reverse Multidrug Resistance in Bacteria - Annamária Kincses; Stefánia Szabó; Bálint Rácz; Nikoletta Szemerédi; Genki Watanabe; Ryosuke Saijo; Hiroshi Sekiya; Eiji Tamai; Joseph Molnár; Masami Kawase; Gabriella Spengler (Antibiotics, 2020)
Bacteria often show resistance against antibiotics due to various mechanisms such as the expression of efflux pumps, biofilm formation, or bacterial quorum sensing (QS) controls. For successful therapy, the discovery of alternative agents is crucial. The objective of this study was to evaluate the efflux pump, anti-biofilm, and QS inhibiting, as well as antibacterial effects of 2-trifluoroacetonylbenzoxazole ligands (1–3) and their metal complexes (4–12) in bacteria. The ligand 2 and its Zn(II) complex 5, and furthermore the Cu(II) complex 7 of ligand 1, exerted remarkable antibacterial activity on the Staphylococcus aureus 272123 (MRSA) strain. In the minimum inhibitory concentration (MIC) reduction assay the ligand 3, the Zn(II) complex 5 of ligand 2, and the Cu(II), Ni(II), Mg(II), Fe(III) complexes (7, 8, 9, 12) of ligand 1 enhanced the antibacterial activity of ciprofloxacin in MRSA. An increased ethidium bromide accumulation was detected for ligand 3 in MRSA while the Fe(III) complex 12 of ligand 1 decreased the biofilm formation of the reference S. aureus ATCC 25923 strain. The Zn(II) and Ag(II) complexes (3 and 4) of ligand 1 and ligand 3 inhibited the QS. Based on our results, the ligands and their metal complexes could be potential alternative drugs in the treatment of infectious diseases.